FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN UNMET NEED PADA PASANGAN USIA SUBUR (PUS) DI PUSKESMAS PERAWATAN AMETH KECAMATAN NUSALAUT - Melawati Wakano; Adolf M Berhitu (STIKES Pasapua Ambon, 2021)
Introduction: Unmet need is a couple of childbearing age (PUS) who do not want children, want children 2 years or more apart but do not use contraception. The unmet need group is a target that needs to be considered in family planning program services (Sariestya, 2014). The aim of this research is to find out the factors related to unmet need in couples of childbearing age (PUS) at the Ameth Care Health Center. Method: This research uses a correlation descriptive method with a “cross sectional” approach, namely by collecting data at one time (Notoadmodjo, 2010). Based on the results of calculations using the SPSS computer program, with the Chi-Square statistical test. Results: the results for the knowledge factor are p-value 0.045, parity is obtained p-value 0.020, and spousal support is obtained p-value 0.003 where the p-value results of these three factors are <0.05 , so that it can be concluded that there is a relationship between knowledge, parity, and husband support with unmet need for couples of childbearing age at the Ameth Care Health Center, Nusalaut District. Conclusion: that there is a relationship between knowledge, parity and husband support with unmet need for couples of childbearing age at the Ameth treatment center in Nusalaut sub-district. So that it can be recommended for families, especially married couples who already have children to run the meet need program properly.